Laser microprocessing of sapphire - Lye, Celescia Siew Mun (Nanyang Technological University, 2020)
Sapphire is a substrate in many applications; for example, in watch covers, phone displays, integrated circuits, optoelectronics and light emitting diodes (LEDs). To be useful for these applications, sapphire boules have to be separated into wafers and chips for further processing. This thesis investigates an important processing step of sapphire, namely the laser singulation of sapphire. Previous studies showed that the surface morphology of patterned sapphire substrates (PSS) enhanced the light emission of LEDs. However, the effects of surface morphology on the optical properties of sapphire during laser scanning have not been properly studied. This thesis examined the interaction between the laser beam and sapphire of different surface roughness. Experiments conducted confirmed the proposed hypothesis in this investigation that a sample with a single rough surface exhibited higher levels of absorbance compared to a sample with two polished surfaces. This is predominantly a result of internal reflection at the exit surface. As such, internal reflection can be enhanced by orientating the sample such that the rough surface was facing away from the laser beam source. The presence of the rough surface encourages nonlinear absorption within the sample at lower incoming laser intensities. Significantly more nonlinear absorption could be observed in the sample with its rough surface facing away from the laser, i.e. with a bottom rough surface. As a result, ablation scribes were observed on both top and bottom surfaces of a sample after picosecond laser irradiation at 1.7 W with a focused spot diameter of 27.1 μm on the top surface of the sample. Therefore, the presence of the bottom rough surface improves the nonlinear interaction between the laser beam and the sample. Previous studies on multiple foci laser cutting of a transparent material have been focused on transparent glass cutting. The foci spots were spread over the glass thickness employing highly specialized focusing optics. However, the investigation of the same for sapphire has been lacking. This is worth investigating, in particular if a rough sidewall profile can be produced as a roughened sidewall profile has been shown to improve the light extraction of LEDs. A detailed study of multiple foci technology has been successfully conducted here for the singulation of 430 μm thick sapphire samples with a 1064 nm picosecond laser. Commercially available multifocal lens and focusing optics were employed for ease of adopting the multiple foci technology. This study highlighted the importance of a low pulse repetition rate (i.e. high pulse energy and high peak power) over a low scanning speed (i.e. more energy deposition) in producing a cleavable sample. Increasing the energy deposition alone was ineffective if high laser intensity was absent to induce nonlinear absorption within the sample. Cleavable samples could be produced by the picosecond laser with a 50 kHz repetition rate, scanning speeds of 1 mm/s or below and at 1.13 W laser power. The focused spot diameters depended on the effective focal length employed. The cleaved samples revealed a non-uniform roughened sidewall profile as a result of nonlinear modification at the various foci spots. Such a profile is desirable for light extraction in LEDs. An innovative proposal for a more effective use of laser energy was explored with multizone scanning. Selected sections of the sample’s thickness were scanned successively, allowing for heat dissipation between scans. For two-zone scanning of samples, two out of three sections of equal thickness were irradiated at 0.57 W for each scan. Each zone consists of 9 foci with a focused spot diameter of 2.20 μm. Diffractive order 0 (i.e. at the focal length of the focusing optic) was focused at the midpoint of each zone. At a 50 kHz pulse repetition rate and 10 mm/s scanning speed, a cleavable sample was produced when only the top two-thirds of the sample’s thickness was scanned, namely with the middle section scanned first and the upper section scanned next. Even only a portion of the thickness was scanned, the cleaved sample revealed a uniformly roughened sidewall profile, spanning across the entire sample’s thickness. Therefore, two-zone scanning produced a cleavable sample with a roughened sidewall profile, simultaneously achieving more desirable results with less energy deposition. To summarize, this study represents the first investigation on the effects of sample surface roughness interaction with a laser beam. The sample with a single rough bottom surface exhibited the highest level of absorptivity as a result of internal reflection at the exit surface. Multiple foci laser technology for sapphire singulation was first explored in this investigation. Nonlinear modification occurred at various foci spots such that cleavable samples revealed a non-uniform roughened sidewall profile. Two-zone scanning of the top two-thirds of the sample only resulted in cleavable samples with a uniformly roughened sidewall profile throughout the sample’s thickness. This is a novel approach of multizone scanning of sapphire samples resulted in improvement of process efficiency and effectiveness.